Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

Multiple successful pregnancies in a woman with biliary atresia and native liver. - Matarazzo, Lorenza; Assandro, Paola; Martelossi, Stefano; Maggiore, Giuseppe; Ventura, Alessandro (Eur J Obstet Gynecol Reprod Biol, 2018)

Ocular Manifestations of Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. - Ottaviano, Giorgio; Salvatore, Silvia; Salvatoni, Alessandro; Martelossi, Stefano; Ventura, Alessandro; Naviglio, Samuele (J Crohns Colitis, 2018)
Background and Aims: Ocular extraintestinal manifestations [O-EIMs] are known complications of Crohn's disease [CD], ulcerative colitis [UC], and inflammatory bowel disease unclassified [IBD-U]. However, data on their prevalence in children are scarce and there are no clear recommendations on what follow-up should be offered. We aimed to review available data on O-EIMs in children. Methods: In January 2018, we performed a systematic review of published English literature using PubMed and EMBASE databases and disease-specific queries. Results: Fifteen studies [7467 patients] reported data on O-EIMs prevalence in children. Overall prevalence of O-EIMs was 0.62-1.82%. Uveitis was the most common O-EIM. Meta-analysis showed that children with CD are at increased risk of O-EIMs as compared with children with UC and IBD-U (odds ratio [OR] 2.70, 95% confidence interval [CI] 1.51-4.83). Five studies [357 patients] reported data on ophthalmological screening in asymptomatic children: mild asymptomatic uveitis was identified in a variable proportion of patients [1.06-23.1%], more frequently in male patients with CD and colonic involvement. No evidence of ocular complications from untreated uveitis was detected. A total of 23 case reports [24 patients] were identified. Conclusions: Data on O-EIMs in children are scarce. Prevalence of O-EIMs is lower than in adults but may be underestimated because of the possibility of asymptomatic uveitis; however, the long-term significance of this condition is unknown. Children with CD may be at increased risk of O-EIMs. No recommendations on routine ophthalmological examination can be made, but a low threshold for ophthalmological referral should be maintained. Larger studies in paediatric IBD populations are needed.
Keywords: Adolescent; Cataract; Child; Child, Preschool; Colitis, Ulcerative; Crohn Disease; Eye Diseases; Humans; Prevalence; Uveitis

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Ocular Involvement in Children with Inflammatory Bowel Disease. - Naviglio, Samuele; Parentin, Fulvio; Nider, Silvia; Rassu, Nicolò; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2017)
BACKGROUND: Data on ocular manifestations of inflammatory bowel disease (IBD) in children are limited. Some authors have reported a high prevalence of asymptomatic uveitis, yet the significance of these observations is unknown and there are no recommendations on which ophthalmologic follow-up should be offered. METHODS: Children with IBD seen at a single referral center for pediatric gastroenterology were offered ophthalmologic evaluation as part of routine care for their disease. Ophthalmologic evaluation included review of ocular history as well as slit-lamp and fundoscopic examination. Medical records were also reviewed for previous ophthalmologic diagnoses or complaints. RESULTS: Data from 94 children were included (52 boys; median age 13.4 yr). Forty-six patients had a diagnosis of Crohn's disease, 46 ulcerative colitis, and 2 IBD unclassified. Intestinal disease was in clinical remission in 70% of the patients; fecal calprotectin was elevated in 64%. One patient with Crohn's disease had a previous diagnosis of clinically manifest uveitis (overall uveitis prevalence: 1.06%; incidence rate: 0.3 per 100 patient-years). This patient was also the only one who was found to have asymptomatic uveitis at slit-lamp examination. A second patient had posterior subcapsular cataract associated with corticosteroid treatment. No signs of intraocular complications from previous unrecognized uveitis were observed in any patient. CONCLUSIONS: Children with IBD may have asymptomatic uveitis, yet its prevalence seems lower than previously reported, and it was not found in children without a previous diagnosis of clinically manifest uveitis. No ocular complications from prior unrecognized uveitis were observed.
Keywords: Adolescent; Child; Child, Preschool; Feces; Female; Humans; Inflammatory Bowel Diseases; Italy; Leukocyte L1 Antigen Complex; Male; Remission Induction; Uveitis

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Fecal Calprotectin: Diagnostic Accuracy of the Immunochromatographic CalFast Assay in a Pediatric Population. - Radillo, Oriano; Pascolo, Lorella; Martelossi, Stefano; Dal Bo, Sara; Ventura, Alessandro (J Clin Lab Anal, 2016)
BACKGROUND: Fecal calprotectin is a noninvasive marker for bowel diseases and it is high valuable to follow disease activity in Crohn's disease (CD) and ulcerative colitis (UC). In this study, we evaluated the diagnostic performance of the recently introduced immunochromatographic assay CalFast in comparison to the well-known ELISA tests for calprotectin assay to obtain a rapid diagnosis of bowel inflammation in pediatric patients. METHODS: CalFast was tested in parallel to the classic ELISA tests CalPrest and PhiCal (gold standards for the calprotectin determination) on 148 fecal samples from pediatric subjects including 104 healthy subjects, 29 with CD, and 15 with UC. RESULTS: In this study, the sensitivity and specificity of CalFast, CalPrest, and PhiCal were 86.4%, 88.6%, and 93.2% and 86.6%, 74%, and 64.4%, respectively. The area under the curve, obtained from receiver operating characteristic analysis, indicated the lack of significant difference among all the kits used. CONCLUSION: The immunochromatographic assay demonstrated good diagnostic predictive values, comparable to those of the ELISA methods, and may represent a valid alternative in order to save operators' time. The test, in fact, has a short turnaround time and does not need a specific ELISA instrumentation.

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Thalidomide for inflammatory bowel disease: Systematic review. - Bramuzzo, Matteo; Ventura, Alessandro; Martelossi, Stefano; Lazzerini, Marzia (Medicine (Baltimore), 2016)
BACKGROUND: Thalidomide is an immunomodulatory drug used in the experimental treatment of refractory Crohn disease and ulcerative colitis. We aimed to review the existing evidence on the efficacy and safety of thalidomide in the treatment of inflammatory bowel diseases. METHODS: CENTRAL, MEDLINE, LILACS, POPLINE, CINHAL, and Web of Science were searched in March 2016. Manual search included conference and reference lists. All types of studies, except single case reports, were included. Outcomes evaluated were: induction of remission; maintenance of remission; steroid reduction; effect on penetrating Crohn disease; endoscopic remission; adverse events. RESULTS: The research strategies retrieved 722 papers. Two randomized controlled trials and 29 uncontrolled studies for a total of 489 patients matched the inclusion criteria. Thalidomide induced a clinical response in 296/427 (69.3%) patients. Clinical remission was achieved in 220/427 (51.5%) cases. Maintenance of remission was reported in 128/160 (80.0%) patients at 6 months and in 96/133 (72.2%) at 12 months. Reduction in steroid dosage was reported in 109/152 (71.7%) patients. Fistulas improved in 49/81 (60.5%) cases and closed in 28/81 (34.6%). Endoscopic improvement was observed in 46/66 (69.7%) and complete mucosal healing in 35/66 (53.0%) patients. Cumulative incidence of total adverse events and of those leading to drug suspension was 75.6 and 19.7/1000 patient-months, respectively. Neurological disturbances accounted for 341/530 (64.3%) adverse events and were the most frequent cause of drug withdrawal. CONCLUSION: Existing evidence suggests that thalidomide may be a valid treatment option for patients with inflammatory bowel diseases refractory to other first- and second-line treatments.

Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.

Coeliac disease in the ERA of the new ESPGHAN and BSPGHAN guidelines: a prospective cohort study. - Benelli, Elisa; Carrato, Valentina; Martelossi, Stefano; Ronfani, Luca; Not, Tarcisio; Ventura, Alessandro (Arch Dis Child, 2015)
OBJECTIVE: To evaluate the consequences of the last European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) guidelines for the diagnosis of coeliac disease (CD) by means of a prospective study. DESIGN: Prospective cohort study. SETTING: Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy). PATIENTS: Children diagnosed with CD without a duodenal biopsy (group 1), following the last ESPGHAN and BSPGHAN guidelines, and children diagnosed with a duodenal biopsy, matched for sex, age and year of diagnosis (group 2), were prospectively enrolled over a 3-year period. All patients were put on a gluten-free diet (GFD) and were followed up for clinical conditions and laboratory testing at 6 months every year since diagnosis (median follow up: 1.9 years). OUTCOME MEASURES: Resolution of symptoms, body mass index, laboratory testing (haemoglobin, anti-transglutaminase IgA), adherence to a GFD, quality of life, and supplementary post-diagnosis medical consultations. RESULTS: 51 out of 468 (11%) patients were diagnosed without a duodenal biopsy (group 1; median age 2.1 years) and matched to 92 patients diagnosed with a biopsy (group 2; median age 2.4 years). At the end of follow-up the two groups were statistically comparable in terms of clinical and nutritional status, anti-transglutaminase IgA antibody titres, quality of life, adherence to a GFD, and number of supplementary medical consultations. CONCLUSIONS: On the basis of this prospective study, diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases. At least during a medium-term follow-up, this approach has no negative consequences relating to clinical remission, adherence to diet, and quality of life of children with CD.

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Reply to Thalidomide Treatment of Pediatric Ulcerative Colitis: A New Use for an Old Drug. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2015)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Multiple Ileo-Ileal Intussusceptions Caused by Eosinophilic Enteropathy. - Bramuzzo, Matteo; Martelossi, Stefano; Villanacci, Vincenzo; Maschio, Massimo; Costa, Stefano; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2014)

Pharmacogenetics of azathioprine in inflammatory bowel disease: a role for glutathione-S-transferase? - Stocco, Gabriele; Pelin, Marco; Franca, Raffaella; De Iudicibus, Sara; Cuzzoni, Eva; Favretto, Diego; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2014)
Azathioprine is a purine antimetabolite drug commonly used to treat inflammatory bowel disease (IBD). In vivo it is active after reaction with reduced glutathione (GSH) and conversion to mercaptopurine. Although this reaction may occur spontaneously, the presence of isoforms M and A of the enzyme glutathione-S-transferase (GST) may increase its speed. Indeed, in pediatric patients with IBD, deletion of GST-M1, which determines reduced enzymatic activity, was recently associated with reduced sensitivity to azathioprine and reduced production of azathioprine active metabolites. In addition to increase the activation of azathioprine to mercaptopurine, GSTs may contribute to azathioprine effects even by modulating GSH consumption, oxidative stress and apoptosis. Therefore, genetic polymorphisms in genes for GSTs may be useful to predict response to azathioprine even if more in vitro and clinical validation studies are needed.
Keywords: 6-Mercaptopurine; Animals; Apoptosis; Azathioprine; Glutathione; Glutathione Transferase; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Oxidative Stress; Pharmacogenetics; Polymorphism, Genetic

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Use of placebo in a trial of thalidomide for pediatric Crohn disease--reply. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (JAMA, 2014)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Amenorrhea in women treated with thalidomide: report of two cases and literature review. - Lazzerini, Marzia; Bramuzzo, Matteo; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Ventura, Alessandro (Inflamm Bowel Dis, 2013)
Keywords: Adolescent; Amenorrhea; Colitis, Ulcerative; Crohn Disease; Female; Humans; Review Literature as Topic; Thalidomide

Family history in early-onset inflammatory bowel disease. - Bianco, Anna Monica; Zanin, Valentina; Monasta, Lorenzo; Martelossi, Stefano; Marcuzzi, Annalisa; Crovella, Sergio (J Gastroenterol, 2013)
Keywords: Colitis, Ulcerative; Crohn Disease; Female; Humans; Male

Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed

A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological

Delayed diagnosis of glycogen storage disease type III. - Minen, Federico; Cont, Gabriele; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro; Maggiore, Giuseppe; Faletra, Flavio; Gasparini, Paolo; Cassandrini, Denise (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Delayed Diagnosis; Diagnostic Errors; Glycogen Storage Disease Type I; Glycogen Storage Disease Type III; Humans; Infant; Liver; Male

Inflammation profile of four early onset Crohn patients. - Marcuzzi, Annalisa; Girardelli, Martina; Bianco, Anna Monica; Martelossi, Stefano; Magnolato, Andrea; Tommasini, Alberto; Crovella, Sergio (Gene, 2012)
Crohn disease (CD) is a multifactorial disorder affecting mainly young adults. Sometimes, however, it can present in the first year of life (Early onset Crohn disease (EOCD)) showing an unpredictable course and can often be more severe than at older ages. Some cases have been associated to an underlying primary immunodeficiency such as IL10R deficiency. We studied the functional response to IL-10 and the genotype of IL-10 receptor in four patients with early onset crohn-like colitis. We found an IL10R variant, which may be associated with a decreased response to the cytokine in one patient. Further studies to determine its pathogenic effect should be performed. In addition IL-10 mediated inhibition of LPS-induced TNFα expression was measured in patient's monocytes.
Keywords: Crohn Disease; Cytokines; Humans; Inflammation; Monocytes; Nod2 Signaling Adaptor Protein; Polymorphism, Genetic; Receptors, Interleukin-10; Tumor Necrosis Factor-alpha

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

Molecular mechanism of glucocorticoid resistance in inflammatory bowel disease. - De Iudicibus, Sara; Franca, Raffaella; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2011)
Natural and synthetic glucocorticoids (GCs) are widely employed in a number of inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in moderate to severe active Crohn's disease and ulcerative colitis. Despite their extensive therapeutic use and the proven effectiveness, considerable clinical evidence of wide inter-individual differences in GC efficacy among patients has been reported, in particular when these agents are used in inflammatory diseases. In recent years, a detailed knowledge of the GC mechanism of action and of the genetic variants affecting GC activity at the molecular level has arisen from several studies. GCs interact with their cytoplasmic receptor, and are able to repress inflammatory gene expression through several distinct mechanisms. The glucocorticoid receptor (GR) is therefore crucial for the effects of these agents: mutations in the GR gene (NR3C1, nuclear receptor subfamily 3, group C, member 1) are the primary cause of a rare, inherited form of GC resistance; in addition, several polymorphisms of this gene have been described and associated with GC response and toxicity. However, the GR is not self-standing in the cell and the receptor-mediated functions are the result of a complex interplay of GR and many other cellular partners. The latter comprise several chaperonins of the large cooperative hetero-oligomeric complex that binds the hormone-free GR in the cytosol, and several factors involved in the transcriptional machinery and chromatin remodeling, that are critical for the hormonal control of target genes transcription in the nucleus. Furthermore, variants in the principal effectors of GCs (e.g. cytokines and their regulators) have also to be taken into account for a comprehensive evaluation of the variability in GC response. Polymorphisms in genes involved in the transport and/or metabolism of these hormones have also been suggested as other possible candidates of interest that could play a role in the observed inter-individual differences in efficacy and toxicity. The best-characterized example is the drug efflux pump P-glycoprotein, a membrane transporter that extrudes GCs from cells, thereby lowering their intracellular concentration. This protein is encoded by the ABCB1/MDR1 gene; this gene presents different known polymorphic sites that can influence its expression and function. This editorial reviews the current knowledge on this topic and underlines the role of genetics in predicting GC clinical response. The ambitious goal of pharmacogenomic studies is to adapt therapies to a patient's specific genetic background, thus improving on efficacy and safety rates.
Keywords: Drug Resistance; Glucocorticoids; Humans; Inflammatory Bowel Diseases; P-Glycoproteins; Polymorphism, Genetic; Receptors, Glucocorticoid; Signal Transduction; Transcription, Genetic

Thromboembolism in pediatric inflammatory bowel disease: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Maschio, Massimo; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2011)
BACKGROUND: Several studies suggest an increased risk of venous and arterial thromboembolism (TE) in adults with inflammatory bowel disease (IBD) compared to the general population. We performed a systematic review of studies on incidence and characteristic of TE in children with IBD. METHODS: We searched Medline, LILACS, EMBASE, POPLINE, CINHAL, and reference lists of identified articles, without language restrictions, in August 2010. RESULTS: Population studies suggest that there is an increased risk of TE in children with IBD compared to controls. TE occurred in children with IBD in all age ranges, mostly (82.8%) during active disease, and more frequently in children with ulcerative colitis (odds ratio [OR] 3.7, 95% confidence interval [CI] 1.8-7.6). At least one specific risk factor for TE was recognized in 50% of cases; two risk factors were present in 24%. Out of 92 published cases of TE in children with IBD, 54.3% occurred in cerebral site, 26% in the limbs, 13% in the abdominal vessels, and the remaining in the retina and lungs. After a first episode of TE, an early recurrence was observed in 11.4% of children, a late recurrence in 10%. A number of different therapeutic schemes were used. Overall mortality was 5.7% and was mostly associated with cerebral TE. CONCLUSIONS: Population studies are needed to clarify the risk of TE in children with IBD, the relative weight of other risk factors, the characteristics of the events, and to define guidelines of therapy and prophylaxis.
Keywords: Adult; Child; Humans; Inflammatory Bowel Diseases; Risk Factors; Thromboembolism

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult